Are Minorities Subjected to, or Insulated from, Racialized Policing in Majority–Minority Community Contexts? - Gaston, Shytierra (The British journal of criminology, 2020)
Racial conflict theories suggest that racialized policing should wane in areas where people of colour are the majority and Whites, the minority. This article examines community-level predictors of racial/ethnic differences in drug arrests from 2011 to 2016 across 86 census tracts in Newark, NJ, a city where most officers and residents are persons of colour. We examine whether racial conflict indicators predict Black, White and Hispanic drug arrests, accounting for other factors. Findings indicate that racialized policing prevails within this majority-minority context. Officers tend to arrest Blacks in communities with greater White and Hispanic residents and Whites in predominantly Black areas. In contrast, Hispanic arrests are not attributable to racialized policing. We conclude with recommendations for future theoretical redevelopment.